Structure community of mudskipper at Coast of Bahak Indah, Tongas, Probolinggo – East Java - Lailatul Maghfirah; Husain Latuconsina; Hamdani Dwi Prasetyo (Sekolah Tinggi Ilmu Pertanian Wuna, 2023)
Mangrove forest is one of the ecosystems in the coastal area that plays an important role as a habitat for iktiofauna, one of which is the gelodok fish community. The purpose of this study was to compare the community structure of mudskippers at Bahak Indah Coast, Tongas, Probolinggo with or without mangrove vegetation. The study was conducted in January–February 2022. The determination of the observation station was carried out purposively, which was determined based on the presence or absence of mangrove vegetation. Observation of the mudskipper community used a systematic sampling method with the help of transects and plots. The analyzed mudskipper community structure data included diversity index, uniformity index and dominance index. The results found 4 species from 2 genera of mudskipper namely Boleophthalmus pectinirostris, Boleophthalmus boddarti, Periophthalmus chrysospilos and Periophthalmodon schlosseri. Mudskipper diversity index at both stations was in the medium category, and was higher at the stations with mangrove vegetation. The uniformity index was included in the high category, and was higher at the stations with mangrove vegetation, and the dominance index was in the low category, and lower at the stations with mangrove vegetation. The results of this study indicate that the coastal waters area with mangrove vegetation contributes to the high diversity and uniformity of the mudskipper community compared to areas without mangrove vegetation.